Curved DNA without AA/TT dinucleotide step. - Brukner, I (1991)
The evidence is accumulating that dinucleotide steps other than AA/TT affect DNA flexure of AnTm (m + n greater than = 4) containing fragments. However, it is not clear whether macroscopic DNA flexure without AA/TT steps might occur. In this paper we demonstrate the anomaly in electrophoretic mobility of non AA/TT repetitive DNA sequences which is a function of sequence phasing. Therefore, our results show that PyPu (TA) and AG/CT steps, angulary separated by close to 180 degrees from Pu/Py (GC) and GG/CC steps, bend DNA, even in the absence of AnTm tracts.